China and India, 2025 : a comparative assessment - Wolf, Charles, Jr., 1924-2016 (Rand Corporation monograph series, 2011)
China and India will exercise increasing influence in international affairs in the coming decades. As prominent members of the G-20, their influence will be manifest in the global economy, in global politics, and in the global security environment. Each country's role on the world stage will also be affected by the progress that it makes and by the competition and cooperation that develop between them. The research described in this monograph focuses on the progress China and India seem likely to achieve from 2010 through 2025, as well as on some of the major problems they may encounter along the way. This research consists of a comparative assessment of their prospects in this period in four domains: demography, macroeconomics, science and technology, and defense spending and procurement. In each domain, the assessment seeks answers to these questions: Who is ahead? By how much? and Why? Often the answers are quantitative, sometimes they are more qualitative, and sometimes they are inconclusive. The monograph concludes with implications for policy and for further research.